PENGARUH LAMA PERENDAMAN DALAM AIR PERASAN BUAH BELIMBING WULUH (Averrhoa bilimbi Linn) DAN LAMA PENYIMPANAN TERHADAP KARAKTERISTIK IKAN TONGKOL (Euthynnus affinis) PADA SUHU RUANG - Sitompul, Yemima Maria Lasmaroha; Sugitha, I Made; Duniaji, Agus Selamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i01.p09, 2020)
This study aims to find out the effect of immersion time in wuluh starfruit juice (Averrhoa bilimbi) and storage time of characteristics mackarel tuna fish ( Euthynnus affinis), as well as to determine the right time of immersion in wuluh starfruit juice and storage time to produce mackarel tuna fish with still acceptable characteristics. The experimental design used in this study was a Completely Randomized Design with 5 level immersion treatments, namely: 0 minutes, 2 minutes, 4 minutes, 6 minutes, and 8 minutes, with the observation time in the 3 and 6 hour. The treatment was repeated 2 times to obtain 20 experimental units. The data obtained were analyzed by variance and if the treatment had an effect on the observed variables then it was continued with the Duncan test. The results of the study with duration of immersion time that produced with still acceptable mackarel tuna fish products was 4 minutes at the time of observation of the 6 hour the water content is 71,5%, the acidity was 5.35, the microbial total was 4,28 log cfu/g or 1.9x10 4 cfu/g, and the total volatile base was 21,57 mg N / 100g which was low and the score of color, smell, texture and scales, the eyes, gills, and body surface mucus can be accepted by the panelists as well as overall acceptance that was preferred. Keywords : mackarel tuna fish, wuluh starfruit, immersion time, storage time, total volatil base